Spike specific IgG3 and nucleocapsid IgG response in serum serve as distinguishing immunological markers between SARS-CoV-2 infection and vaccination - Marjahan Akhtar; Md. Rashedul Islam; Fatema Khaton; Fatima Rahman; Tausif Adnan Sami; Imam Tauheed; Tasnuva Ahmed; Afroza Akter; Ishtiakul Islam Khan; Zahid Hasan Khan; Prasanta Kumar Biswas; Edward T. Ryan; et al. (Frontiers in Immunology)
BackgroundBoth SARS-CoV-2 infection and COVID-19 vaccines elicit immunological responses. However, it is difficult to distinguish responses generated after vaccination versus natural infection.MethodsWe investigated SARS-CoV-2 spike receptor-binding domain (RBD) and nucleocapsid-specific IgG and RBD specific IgG subclasses (IgG1, IgG2, IgG3 and IgG4) responses using ELISA in four different groups; (1) COVID-19 patients (n=39) with varying disease severity and (2) COVID-19 vaccinated individuals (n=24, both adenovirus/mRNA based) (3) vaccinated after infection (n=39) and (4) patients experienced breakthrough infection (n=14), in Bangladesh.ResultsBoth COVID-19 patients and vaccinees developed robust RBD-specific IgG responses. In contrast, nucleocapsid specific IgG responses were found in patients but not in vaccine recipients. A distinct IgG subclass antibody response was observed in COVID-19 patients compared to COVID-19-vaccinated individuals. Specifically, COVID-19 patients exhibited elevated levels of both IgG1 and IgG3, with IgG3 dominating in the early phase of infection (days 1-7) followed by a subsequent increase in IgG1. Conversely, COVID-19 vaccination predominantly induced IgG1 responses without a concurrent rise in IgG3. This effect was more evident when a significant rise of IgG1 but not IgG3 was observed in patients who received COVID-19 vaccines after 90 days of infection. However, following breakthrough infection, we observed an increase in both IgG1 and IgG3. All of these findings collectively indicate that COVID-19 vaccination predominantly induces IgG1, whereas natural infection can elicit responses in both IgG1 and IgG3 subclasses.ConclusionThe findings highlight RBD-specific IgG3 as well as nucleocapsid IgG as crucial markers for differentiating between vaccination and natural infection and suggest these assays have utility for longitudinal monitoring of vaccinations and for establishing SARS-CoV-2 correlates of protection.